Weight Optimization of Optimal Control Influenza Model Using Artificial Bee Colony - Dinita Rahmalia; Teguh Herlambang ((IJCSAM) International Journal of Computing Science and Applied Mathematics, 2018)
Influenza is disease which can be contagious through contact with infected individual. There are two types of control strategies to bound the spread of disease: prevention action for controlling susceptible and treatment for controlling infected. Optimal control is used for minimizing the number of infected individual, the cost of prevention action and the cost of treatment. Due to the cost of objective function depends on weight, in this research we will apply Artificial Bee Colony algorithm to optimize weight minimizing cost of objective function. The simulations show that the number of infected with control is lower than without control. Furthermore, we also obtain optimal weight related to cost of prevention action and treatment.